Association between reproductive variables and metabolic syndrome in chinese community elderly women. (March 2016) - Liu, Miao; He, Yao; Jiang, Bin; Wu, Lei; Wang, Jianhua; Yang, Shanshan; Wang, Yiyan; Li, Xiaoying
Highlights: First study to assess relationship of reproductive factors and MetS in large Chinese elderly. There is a strong association between reproductive factors and higher MetS risk in Chinese women. Simple information on menarche timing could help identify women with higher risk of getting MetS. Abstract: Objective: This study aimed to evaluate the association between reproductive variables and metabolic syndrome (MetS) among Chinese community elderly women. Methods: We conducted a cross-sectional study in a Beijing urban district. A two-stage stratified clustering sampling method was used and 1251 elderly women were included. Results: The prevalence of MetS was 65.1% in this population. Women with MetS had younger menarche age, a greater number of years after menopause, higher gravidity and parity. The prevalence of MetS showed an increasing trend for tertiles of years after menopause ( p = 0.002) and number of children ( p < 0.001), while decreasing trend for menarche age ( p = 0.021). Logistic regression showed ORs of age at menarche, years after menopause and number of children for MetS were 0.94, 1.40, and 1.36 for second and 0.63, 1.58, and 1.75 for last tertiles. Conclusion: There is strong association between reproductive variables and higher risk of MetS. Simple information on timing of menarche and menopause could help identify women who may have higher risk of getting MetS and take early action to prevent related chronic diseases.